Prevalence of mood symptoms in patients with cannabis use admitted to the acute wards at Free State psychiatry complex with schizophrenia spectrum and related disorders - Pooe, M. T. (University of the Free State, 2021)
Background: Cannabis is the most commonly used drug among psychotic patients. Literature shows that the frequency and intensity of cannabis use, is a risk-factor for the development of schizophrenia-related psychosis. However, evidence for causality of mood disorders remain conflicting. Aim: The purpose of this study was to compare the prevalence and severity of mood symptoms in patients with schizophrenia spectrum and related disorders with comorbid cannabis use and those that does not use cannabis. Setting: This study was conducted in patients with schizophrenia spectrum and related disorders admitted at the acute wards at the Free State Psychiatric complex. Methods: A prospective study was conducted among 30 non- cannabis users and 40 cannabis users. The Young Mania Rating Scale (YMRS) and Hamilton Depression (HAM-D) rating scale for depression was administered within three days of admission and repeated after 7-14 days. Results: Among cannabis users, symptoms compatible with mania like symptoms was significantly more prevalent shortly after admission with (p<0.01). However, this difference declined to non-significance after 7 – 14 days with no clinical separation between the groups. Conclusion: Seventy-five percent of schizophrenia spectrum and related disorders patients that used cannabis, scored ≥18 on the YMRS shortly after admission. Mania like symptoms were of mild-moderate severity. The study indicated a possible association between cannabis use and higher scores on the YMRS rating scale during the early phase of treatment. A causal link between mood symptoms and cannabis use could not be established and confounding factors were not excluded.
Dissertation (M.Med. (Psychiatry))--University of the Free State, 2021
Keywords: Cannabis; Mania; Depression; Psychosis; Hypomania; Prospective study; Free State Psychiatric Complex; Bipolar mood disorder; Major depressive disorder; Acute